Predicting the potential hybridization zones between native and invasive marmosets within Neotropical biodiversity hotspots - Moraes, Andreia Magro [UNESP]; Vancine, Maurício Humberto [UNESP]; Moraes, Andreza Magro; de Oliveira Cordeiro, Carlos Leandro [UNESP]; Pinto, Míriam Plaza; Lima, Adriana Almeida; Culot, Laurence [UNESP]; Silva, Thiago Sanna Freire [UNESP]; Collevatti, Rosane Garcia; Ribeiro, Milton Cezar [UNESP]; Sobral-Souza, Thadeu (Elsevier, 2019)
The human-induced introductions of marmoset species (Callithrix genus) threaten the native species persistence within Brazilian biodiversity hotspots. Invasive marmosets can hybridize with native congeners reducing the genetic integrity on native populations. However, no study quantified the spatial extent of these invasions and which species can be impacted by a hybridization process. Here, we predicted the range expansion and hence the potential geographic overlap between Callithrix species, particularly in Atlantic Forest and Cerrado, to discuss management strategies. We hypothesized that marmosets endemic to the Atlantic Forest are more threatened by invasive congeners than other marmosets. We generated species distribution models for six Callithrix species using four algorithms, six environmental layers and 445 georeferenced localities extracted from literature published since 2000. Suitability maps for each species were binarized using a 20-percentile threshold and overlapped to predict invasion and quantify hybridization potential risks. All Callithrix species had potential to expand their range within the Atlantic Forest although suitable habitats for C. flaviceps and C. kuhlii were more limited. C. jacchus and C. penicillata have already expanded their range to different biomes and our model shows that they can spread even further. The potential hybridization zones were identified within the distribution range of all species, and more markedly within Atlantic Forest species ranges. For assuring the ecosystem equilibriums, we urge to prevent the biological invasions and to control the human-induced Callithrix introductions and expansions within Neotropical hotspots.
Keywords: Biological invasion; Habitat suitability; Hybridization risk; Primate conservation; Species distribution model